Pelatihan Part of Speech pada Siswa SMA di Desa Situ Udik Kecamatan Cibungbulang Kabupaten Bogor di Masa Pandemi Covid-19 - Fifin Mulyati; Adinda Fitri; Alma Nurul, dkk; Nina (STKIP Muhammadiyah Bogor, 2021)
The Covid-19 pandemic has brought about major changes in political, socioeconomic, educational, and other aspects of our “normal” daily life. In the education sector, the pattern of face-to-face learning in the classroom, many have stopped due to the recommendation of physical distancing as an effort to prevent the transmission of Covid-19. Through theStudent Study Service(KKN-Dik) based on Studysaster STKIP Muhammadiyah Bogor students, the Cibungbulang sub-district group has a superior program, namely Part of Speech training for high school students. This part of the Speech material training activity aims to help increase interest and understanding in learning English for high school students in Situ Udik Village, Cibungbulang District, Bogor Regency. This activity was carried out in two meetings, namely on October 1, 2021, and October 4, 2021. The method used in the Part of Speech training activity was a descriptive qualitative method. In analyzing the final result data using pre-test - post test. Based on data analysis, the results of the Part of Speech training activity are beneficial for students in Situ Udik village, Cibungbulang district, Bogor Regency because there is an increase in understanding in the introduction of English about words that are categorized according to their roles and functions in the sentence structure of a language.